PERSIAPAN LAHAN KETAHANAN PANGAN SANTRI DI MARKAZ PENGHAFAL AL QURAN - Masdania Zurairah; Margi Subahagia; Rizkha Rida; Muhammad Said; Desi Ardilla (Bajang Institute, 2024)
Devotion is an activity that is highly expected to be carried out well, because it can improve and add to knowledge and skills. The male students at the Al Quran memorization headquarters are the driving force to open up land that has not been utilized properly. The location of the land for strengthening food security that will be carried out is close to the location of the Al Quran memorization headquarters, making it easier to move to the land location. The beginning of this movement is land preparation or clearing land from undergrowth using tripe, machetes and hoe so that clean land is obtained and ready to be planted. The types of plants that will be planted in this food security strengthening are cassava, sweet potatoes or yams, corn, taro, peanuts and green beans.